2019
DOI: 10.1021/acs.est.8b06197
|View full text |Cite
|
Sign up to set email alerts
|

Criteria Air Pollutants and Greenhouse Gas Emissions from Hydrogen Production in U.S. Steam Methane Reforming Facilities

Abstract: The global and U.S. domestic effort to develop a clean energy economy and curb environmental pollution incentivizes the use of hydrogen as a transportation fuel, owing to its zero tailpipe pollutant emissions and high fuel efficiency in fuel cell electric vehicles (FCEVs). However, the hydrogen production process is not emissions free. Conventional hydrogen production via steam methane reforming (SMR) is energy intensive, coproduces carbon dioxide, and emits air pollutants. Thus, it is necessary to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(49 citation statements)
references
References 9 publications
0
49
0
Order By: Relevance
“…Many non peer-reviewed reports give estimates for carbon dioxide emission from gray hydrogen that are in the range of 10 tons carbon dioxide per ton of hydrogen, 1,7 although data in support of these values are generally absent, perhaps because they are based on confidential information. 11 Since the gross calorific heat energy content of hydrogen is 0.286 MJ per mole, 17 10 tons of carbon dioxide per ton of hydrogen corresponds to 70 g CO 2 per MJ. This is similar to but somewhat lower than our value of 75.6 g CO 2 per MJ.…”
Section: Total Carbon Dioxide and Methane Emissions For Gray Hydrogenmentioning
confidence: 99%
See 2 more Smart Citations
“…Many non peer-reviewed reports give estimates for carbon dioxide emission from gray hydrogen that are in the range of 10 tons carbon dioxide per ton of hydrogen, 1,7 although data in support of these values are generally absent, perhaps because they are based on confidential information. 11 Since the gross calorific heat energy content of hydrogen is 0.286 MJ per mole, 17 10 tons of carbon dioxide per ton of hydrogen corresponds to 70 g CO 2 per MJ. This is similar to but somewhat lower than our value of 75.6 g CO 2 per MJ.…”
Section: Total Carbon Dioxide and Methane Emissions For Gray Hydrogenmentioning
confidence: 99%
“…Most of these non peer-reviewed reports do not include methane in their estimates, 1 or if they do, they provide no detail as to how they do so. The most thorough peer-reviewed analysis of carbon dioxide emissions for gray hydrogen is that of Sun et al 11 who obtained data on both rates of hydrogen production and emissions of carbon dioxide from many individual facilities across the United States. They concluded that on average, carbon dioxide emissions for gray hydrogen are 77.8 g CO 2 per MJ, remarkably close to our value of 75.6 g CO 2 per MJ.…”
Section: Total Carbon Dioxide and Methane Emissions For Gray Hydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…When compression is needed for H 2 storage, it does undercut the benefits of importing H 2 in terms of both cost and GHG emissions. The CIs (g CO 2 e/MJ H 2 ) of potential H 2 sources, including both production and transmission to corn ethanol plants, are calculated using the GREET model 20,35‐39 and presented in Fig. 4.…”
Section: Methodsmentioning
confidence: 99%
“…Emissions The annual diesel genset CO2 emissions are calculated from the diesel consumption with an emission factor equal to 3.2 kg of CO2 per kg of diesel [18]. The FCS CO2 emissions, due to the fuel processing system, are estimated with an emission factor of 0.56 kg of CO2 per kWh of produced electricity [19]. Finally, the genset NOx emissions are estimated by considering a NOx emission factor of 2 g per each kWh of produced electricity [20], while FCS NOx emissions can be assumed as negligible.…”
Section: Methodsmentioning
confidence: 99%